A Refinement of Collaborative Circles Theory: Resource Mobilization and Innovation in an Emerging Sport. (March 2013) - Corte, Ugo
Farrell's (2001) theory of collaborative circles provides a useful frame for analyzing the interpersonal dynamics that enable creative collaboration in small groups, but it leaves contextual factors of collaboration undertheorized. Using ethnographic data on freestyle BMXers in Greenville, North Carolina, this article demonstrates how resource mobilization theory's conception of resources can specify the enabling and constraining aspects of a circle's environment in a theoretically satisfying way. Specifically, I find that the enabling interpersonal dynamics found by Farrell rely on distinct arrangements of material, moral, and what I term locational resources. During the formation stage, a welcoming skatepark and moral support from the local community afforded the group the space and time it needed to unite, articulate a common vision, and produce dramatic innovations in their sport. During the separation stage, increased resources from the commercialization of freestyle BMX influenced both the separation of the circle and the production of the scene that followed.